The impact of immigration on election outcomes in Danish municipalities - Christer Gerdes; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2008)
In this paper we study the effects on support for different political parties due to an increase in the immigrant share in Danish municipalities during the period 1989-2001. We find that the immigrant share has some notable effects. The anti-immigration parties are among those that win votes when the immigrant share increases, but a pro-immigration party on the left also gains from an increase in the immigrant share. The non-socialist party that is most pro-immigration, however, loses votes when the immigrant share increases. Our results indicate that in the elections some Danish voters voice their displeasure about immigration in their own neighbourhood. But we find no clear indication of a general decline in support for the welfare state on account of immigration, as several scholars have been predicting.
urn:nbn:de:101:1-20080711112
Keywords: J15; 330; Immigration; immigrants; elections; racism; xenophobia; Migranten; Ethnische Diskriminierung; Wahlverhalten; Kommunalwahl; Dänemark